Increased tau-induced inflammatory responses are associated with a greater degree of atherosclerosis in progressive supranuclear palsy - Yi-Xin He; Yi-Xin He; Rui Zhang; Rui Zhang; Chen Xie; Si-Fan Ji; Wen-Jing Deng; Wen-Jing Deng; Jun-Fang Teng; Jun-Fang Teng (Frontiers in Aging Neuroscience)
IntroductionIt has been reported that progressive supranuclear palsy (PSP) has a higher prevalence of cerebrovascular disease (CVD); however, the relationship between PSP and atherosclerotic disease remains poorly understood. This study aimed to evaluate the burden of atherosclerosis in patients with PSP and explore the potential role of tau-induced inflammation in its pathogenesis.MethodsWe conducted a cross-sectional study involving 56 patients with PSP and 56 age- and sex-matched healthy controls. Carotid and cerebral atherosclerosis was assessed using ultrasound and magnetic resonance angiography, including measurements of maximum carotid intima-media thickness (max-CIMT), maximum carotid plaque thickness (max-CPT), total plaque number (TPN), carotid plaque score (CPS), maximum carotid stenosis percentage, and global stenosis score (GSS). Plasma levels of traditional atherosclerosis risk factors, total tau, phosphorylated tau (p-tau181, p-tau396), inflammatory cytokines and macrophage proportions were measured. To further investigate the mechanism, we established a mouse model using repeated tail vein injections of tau-preformed fibrils (tau-PFFs), followed by histological and biochemical analysis after 3 months.ResultsCompared to controls, patients with PSP exhibited significantly higher atherosclerotic burden across most measured vascular parameters. Plasma levels of total tau, p-tau181, macrophage proportions and pro-atherogenic inflammatory markers were elevated in patients with PSP. Among them, elevated interleukin-6 (IL-6) levels were positively correlated with the atherosclerosis severity and total tau levels in patients with PSP. In the tau-PFFs mouse model, localized thickening of the aortic wall, increased circulating macrophages, and enhanced inflammatory responses in both plasma and vascular tissues were observed at 3 months post-injection.ConclusionOur findings suggest that patients with PSP reveals increased atherosclerotic burden, potentially mediated by tau-induced systemic inflammation and macrophage activation. Monitoring tau levels and inflammatory markers may serve as a valuable approach for assessing vascular risk in patients with PSP. Furthermore, targeting tau-related inflammatory pathways may offer a novel therapeutic strategy for mitigating atherosclerosis in this population.